PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI SEKOLAH DASAR - Hasti Chumairah; Marzuki Marzuki; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this study was to obtain information about the influence of the scientific approach to learning outcomes and how much influence the scientific approach has on the learning outcomes of Pancasila and Citizenship Education. The conclusion: The influence of the scientific approach to the learning outcomes of pancasila and citizenship Education in fourth grade students of 17 Pontianak State elementary school was 1.69. It can be seen from the results of regression analysis calculations, There is the influence of the scientific approach to the learning outcomes of Pancasila and Citizenship Education in the fourth grade teacher of Pontianak public elementary school with a contribution of 16.9%.Keywords: Learning Outcomes, Pancasila and Citizenship Education, Scientific Approach